Adaptif Conservation (Acm) Model in Increasing Family Support and Compliance Treatment in Patient with Pulonary Tuberculosis in Surabaya City Region - Siti Nur Kholifah; Minarti Minarti; Hilmi Yumni (Universitas Airlangga, 2012)
Introduction: Tuberculosis (TB) in Indonesia is still health problem and the prevalence rate is high. Discontinuing medication and lack of family support are the causalities. Numbers of strategies to overcome are seemingly not succeeded. Roles and responsibilities of family nursing are crucial to improve participation, motivation of individual, family and community in prevention, including pulmonary tuberculosis. Unfortunately, models of pulmonary tuberculosis currently unavailable. The combination of adaptation and conservation in complementarily improving family support and compliance in medication is introduced in this study.Method: This research intended to analyze Adaptive Conservation Model (ACM) in extending family support and treatment compliance. Modeling steps including model analysis, expert validation, ﬁeld trial, implementation and recommending the output model. Research subject involves 15 families who implement family Assistance and supervision in Medication (ASM) and other 15 families with ACM.Result: The study revealed ACM is better than ASM on the case of family support and medication compliances. It supports the role of environment as inﬂuential factor on individual health belief, values and decision making. Therefore, it is advised to apply ACM in enhancing family support and compliance of pulmonary TB patients.Discusion: Social and family supports to ACM group obtained by developing interaction through communication. Family interaction necessary to improve family support to pulmonary tuberculosis patients. And social support plays as motivator to maintain compliance on medication